Socioeconomic disadvantage in infancy on academic and self-regulation outcomes - Olsson, Craig A; McIntosh, Jennifer; Chong, Shiau; Goldfeld, Sharon; O'Connor, Meredith; Hutchinson, D; Sanson, A (My University, 2019)
Objectives: A comprehensive understanding of how timing of exposure to disadvantage effects long term developmental risk is needed for greater precision in child health policy. We investigated whether socioeconomic disadvantage in infancy (age 0-1 years) directly effects academic and self-regulation problems in late childhood (age 10-12 years), independent of disadvantage at school entry (age 4-6 years). Method: Analyses were replicated in two population-based cohorts: the Australian Temperament Project (ATP, N=2443) and the Longitudinal Study of Australian Children (LSAC, N=5107). Generalized linear models (GLM) were used to estimate the crude and adjusted effects. Marginal structural models were used to estimate the controlled direct effect of socioeconomic disadvantage in infancy on academic and self-regulation outcomes in late childhood, independent of disadvantage at school entry. Results: In both cohorts, socioeconomic disadvantage in infancy and at school entry was associated with poorer academic and self-regulation outcomes. Socioeconomic disadvantage in infancy had a direct effect on academic outcomes, not mediated by disadvantage at school entry (ATP: RR=1.42, 95% CI 1.09, 1.86; LSAC: RR=1.87, 95% CI 1.52, 2.31). Little evidence was found for a direct effect of disadvantage in infancy on self-regulation (ATP: RR=1.22, 95% CI 0.89, 1.65; LSAC: RR=1.19, 95% CI 0.95, 1.49). Conclusions: Socioeconomic disadvantage in infancy had a direct effect on academic, but not self-regulation outcomes in late childhood. These findings support the potential for more precise public policy responses. Nuanced strategies need to consider both the timing of children’s exposure to disadvantage and the specific developmental domain impacted.
Keywords: Child Development; Children -- Outcomes; Disadvantage, adversity and resilience